Angel Falls : a novel - Hannah, Kristin (Ballantine reader's circle., 2011)
Dr. Liam Campbell, desperate to reach his wife Mikaela after an accident that has left her in a lingering coma, contacts her ex-husband, movie star Julian True, and then must deal with the consequences when she wakes up with retrograde amnesia, remembering nothing of the past fifteen years, including her marriage and children with Liam.